Focal Myoclonus and Cortical Dysplasia - J Gordon Millichap (Pediatric Neurology Briefs, 1988)
Four patients aged 9 to 19 years with focal myoclonus and intractable focal motor seizures beginning at age 4 to 6 years were treated surgically at the Montreal Neurological Hospital and Institute, McGill University, Montreal, Quebec, Canada.